Leadership in agricultural machinery circles: experimental evidence from Tajikistan - Malte Müller (Australian Journal of Agricultural and Resource Economics, 2020)
Leadership is critical for the viability of rural groups. The way in which leadership is legitimised can mediate leader and group member behaviour in the face of social dilemmas. Yet there has been scant research on leader-follower dynamics in naturally occurring groups. Highlighting the case of agricultural machinery circles in Tajikistan, the effect of leading by example on investments to a collective good is studied in a framed field experiment. To increase realism,~and contrary to standard economic experiments,~this investment is a voucher allowing the group to make a real-world machinery purchase at reduced costs. Two treatments manipulate leaders' legitimisation. Elected leaders achieve 30 per cent higher contributions to the collective investment against a baseline version without a leader. Contributions remain, on average, relatively stable over the course of the game. The results are discussed with reference to the debate on external intervention in agricultural producer organisations.
Keywords: 330; field experiment; public goods game; leading by example; voting; producer organisations; rural development